Comparing accountants' perceptions towards marketing and advertising in Hong Kong and Malaysia - Abdul Aziz Ab Latif; Oliver H.M.Yau; Thomas C.H. Wong; Abdul Latif Shaikh Muhamed Al-Murisi (2008)
The objectives of the paper are to study how CPA firms in Hong Kong and Malaysia perceive the concepts of advertising and marketing; how they perceive the effects of advertising and marketing of their services on professional ethics; and to compare the accountants' perceptions towards marketing and advertising in these two countries. A structured questionnaire consisting of 27 statements was used to measure the attitudes of CPA firms towards marketing and advertising using a Likert scale ranging from "strongly agree" to "strongly disagree." In Hong Kong, the sample was drawn by using systematic 1 in 3 sampling technique from the Hong Kong Yellow Pages telephone directory which provided 120 firms. A response rate of 75% was recorded. In Malaysia, the sample was drawn from the Directory of Accountants, Tax Consultants and Tax Advisers, which provided a sample .of 416. Eighty-six successful responses were received, which gives an acceptable response rate o 20.67 percent. Findings indicated that Malaysian CPAs tend to be more consumer-oriented than their counterparts in Hong Kong.